Thalamic iron in multiple sclerosis: Waning support for the early-rise late-decline hypothesis - Fahad Salman; Niels Bergsland; Michael G. Dwyer; Jack A Reeves; Abhisri Ramesh; Dejan Jakimovski; Bianca Weinstock-Guttman; Robert Zivadinov; Ferdinand Schweser (NeuroImage: Clinical)
Background: Studies of thalamic iron levels in multiple sclerosis (MS) have yielded variable findings, potentially due to differences in study cohorts. For example, studies in relatively young cohorts (average ages below 40 years) have reported elevated susceptibility in people with MS (pwMS), whereas studies in older cohorts (above 40 years) found decreased susceptibility. Objective: To test the “early-rise late-decline” hypothesis, which posits that age differences in study cohorts are responsible for conflicting findings regarding thalamic susceptibility in MS. Methods: We chose to replicate one of the previous studies that showed evidence of elevated thalamic iron concentrations in younger pwMS (Rudko et al., 2014). We also replicated a study involving older pwMS (Pudlac et al., 2020) to serve as a control. We assessed thalamic susceptibility using the QSM processing and analysis methodology outlined by Rudko et al. Results: Although cohort characteristics, QSM processing, and analytical methods were closely matched, we found significantly lower thalamic susceptibility in the younger pwMS compared to controls (−1.1 ± 7.8 vs. 5.4 ± 6.1 ppb; effect sizes: −0.35 to −0.91). Study outcomes were robust across a wide range of regularization parameters, with effect size differences influenced by background field removal regularization. A similar pattern was observed in the older cohort, where thalamic susceptibility was again lower in pwMS compared to controls (4.0 ± 9.5 vs. 9.6 ± 10.7 ppb; effect size: −0.55). Conclusions: Our findings contradict the “early rise” hypothesis of thalamic iron levels in pwMS. The consistency of our results across multiple analyses suggests that QSM processing artifacts are unlikely to explain previous reports of increased thalamic iron. Instead, these variations may stem from demographic or clinical differences, such as geographical factors and treatment regimens.